Target-enrichment sequencing yields valuable genomic data for challenging-to-culture bacteria of public health importance. Issue 5 (27th May 2022) - Dennis, Tristan P. W.; Mable, Barbara K.; Brunelle, Brian; Devault, Alison; Carter, Ryan W.; Ling, Clare L.; Mmbaga, Blandina T.; Halliday, Jo E. B.; Oravcova, Katarina; Forde, Taya L.
Abstract : Genomic data contribute invaluable information to the epidemiological investigation of pathogens of public health importance. However, whole-genome sequencing (WGS) of bacteria typically relies on culture, which represents a major hurdle for generating such data for a wide range of species for which culture is challenging. In this study, we assessed the use of culture-free target-enrichment sequencing as a method for generating genomic data for two bacterial species: (1) Bacillus anthracis, which causes anthrax in both people and animals and whose culture requires high-level containment facilities; and (2) Mycoplasma amphoriforme, a fastidious emerging human respiratory pathogen. We obtained high-quality genomic data for both species directly from clinical samples, with sufficient coverage (>15×) for confident variant calling over at least 80% of the baited genomes for over two thirds of the samples tested. Higher qPCR cycle threshold ( Ct ) values (indicative of lower pathogen concentrations in the samples), pooling libraries prior to capture, and lower captured library concentration were all statistically associated with lower capture efficiency. The Ct value had the highest predictive value, explaining 52 % of the variation in capture efficiency. Samples with Ct values ≤30 were over six times more likely to achieve the threshold coverage than those with a Ct > 30. We conclude that target-enrichment sequencing provides a valuable alternative to standard WGS following bacterial culture and creates opportunities for an improved understanding of the epidemiology and evolution of many clinically important pathogens for which culture is challenging.